PERANCANGAN APLIKASI PENGISIAN KRS KHS BERBASIS ONLINE - Mufria J Purba (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2016)
Development of Science and Technology in this era of globalization affect people's lives in all fields. Everything is expected to be done quickly and accurately (appropriate technology) to all areas of life. To be able to survive and compete in the business world requires the development of strategies and expected to take advantage of technological developments.The world of education is also a field that must continue to innovate with technology. One way that can be used in the use of technology in education is the filling of KRS and KHS online, so as to optimize the performance of students and employees.KRS application design and KHS is intended to improve the performance of a campus to be more effective. Therefore students should not come to campus to take the form and fill in KRS. Students are also able to see KHS anywhere. In addition to the management side can also optimize the data storage of any student who is active and alumni of the college.